# 33n+32np+37n-45n+18np=

## Simple and best practice solution for 33n+32np+37n-45n+18np= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 33n+32np+37n-45n+18np= equation:

Simplifying
33n + 32np + 37n + -45n + 18np = 0

Reorder the terms:
33n + 37n + -45n + 32np + 18np = 0

Combine like terms: 33n + 37n = 70n
70n + -45n + 32np + 18np = 0

Combine like terms: 70n + -45n = 25n
25n + 32np + 18np = 0

Combine like terms: 32np + 18np = 50np
25n + 50np = 0

Solving
25n + 50np = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '25n'.
25n(1 + 2p) = 0

Ignore the factor 25.
Subproblem 1Set the factor 'n' equal to zero and attempt to solve:

Simplifying
n = 0

Solving
n = 0

Move all terms containing n to the left, all other terms to the right.

Simplifying
n = 0
Subproblem 2Set the factor '(1 + 2p)' equal to zero and attempt to solve:

Simplifying
1 + 2p = 0

Solving
1 + 2p = 0

Move all terms containing n to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 2p = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 2p = 0 + -1
2p = 0 + -1

Combine like terms: 0 + -1 = -1
2p = -1

Add '-2p' to each side of the equation.
2p + -2p = -1 + -2p

Combine like terms: 2p + -2p = 0
0 = -1 + -2p

Simplifying
0 = -1 + -2p

The solution to this equation could not be determined.

This subproblem is being ignored because a solution could not be determined.Solutionn = {0}`